Legal Education through Creed: Reforming Religious Pedagogy in Pluralistic Societies - Rahman, Md. Marsudur; Shipon, Md. Amjad Hossain (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Research Objective: To examine the Center for General Education (CGED) at the International Islamic University Chittagong (IIUC) and evaluate how compulsory creed-based courses influence non-Shariah students' legal awareness, ethical behavior, and normative understanding. Research Method: Mixed-methods empirical approach utilized structured questionnaires, validated religious cognition scales, and semi-structured interviews. Analysis focused on students' internalization of legal norms, theological clarity, and behavioral transformation. Results: Students who completed CGED courses exhibited improved comprehension of Islamic legal principles, stronger ethical reasoning, and greater adherence to civic and religious norms. Participants demonstrated increased ability to distinguish between legitimate religious obligations and cultural misconceptions. Positive spillover effects were reported on families and social circles. Findings and Implications: Integration of classical sources, interactive pedagogy, and digital tools enhanced student engagement and legal literacy. Legally structured creed education has broader societal implications and promotes religious moderation and legal consciousness in pluralistic societies. Conclusion: Creed-based education, when legally structured and pedagogically sound, significantly improves students' moral and civic development. Islamic legal epistemology remains relevant in modern university contexts, offering a viable model for educational policy reform. Contribution: Provides empirical evidence for integrating religious instruction into national university curricula while addressing legal and educational challenges in South Asian Islamic higher education. Limitations and Suggestions: Limited to a single institution (IIUC), restricting generalizability. Focusing on non-Shariah students may not represent broader populations. Future research should examine multiple institutions and investigate long-term behavioral sustainability.